Polycyclic aromatic hydrocarbons in four different types of Croatian dry-cured hams - Poljanec, Ivna (Array, 2019)
Polycyclic aromatic hydrocarbons (PAHs) represent an important contaminant group in a variety of food products. Since PAHs are commonly present in meat products, this study aimed to determine PAH content in four types of Croatian dry-cured hams (Dalmatian, Drniš, Krk and Istrian) produced by four different processing methods. Determination and quantification of PAHs were performed by High performance liquid chromatography with fluorescence detection (HPLC-FLD). Out of 15 investigated PAHs, 13 compounds were detected. The total average benzo(a)pyrene (BaP) and PAH4 levels obtained from dry-cured hams ranged from 0.05-0.10 µg/kg and 0.41-0.67 µg/kg, respectively. Even though Krk and Istrian dry-cured ham manufacturing processes do not include the smoking phase, no significant differences were found between investigated dry-cured hams in terms of BaP, PAH4, PAH8 and PAH 15 contents. The presence of detected PAHs in non-smoked dry-cured hams could be a result of the addition of spices in the salting phase. BaP and PAH4 contents found in dry-cured ham samples did not exceed the currently legal levels according to the European legislation.